O destino da missão: a visita padre Gouveia á Província Jesuítica do Brasil na narrativa de Fernão Cardim (1583-1585) - Santana, Jefferson Mariano (2017)
The purpose of this dissertation is to present, through the Narrative by Fernão Cardim, his secretary, with whom he was present as the visit of Father Cristóvão de Gouveia, designated Visitor of the Province of Brazil by the General of the Company of Jesus, Cláudio Aquaviva, between 1583 and 1585. It was proposed to analyze the situation encountered by the Visitor and Fernão Cardim, facing a scenario that had internal problems of the Company of Jesus, such as the lack of missionary fervor, the use of slave labor by autochthons and negroes of Guinea and external problems with the conflict between settlers and Jesuits by exploiting the work of the Indians and their temporal administration in the villages. In this sense, this work shows how the visitor Cristóvão de Gouveia solved the problems in the province, starting from his effective action in spaces important for the missionary project as, for example, the villages, sugar mills, colleges, with measures that aimed to provide the realization of catechesis and, above all, to undertake the colonization of Brazil, which is why the intense participation of the Portuguese Crown in this missionary process is justified